The factors influencing visitation for Kilim Karst Geoforest Park through domestic visitors - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Shuib, Ahmad; Samdin, Zaiton (2014)
Geopark is a classified site for protection of geological resources. It is a region in which the geologic heritage is handled in a sustainable way based on concept of “protection, education and sustainable development”. The Geopark is managed in partnership with the United Nations Educational, Scientific, and Cultural Organization (UNESCO). The Kilim Karst Geoforest Park (KKGP) offers amenities and recreational activities for people to participate. The functions of KKGP in recreation and tourism activities are always related to public goods. This study is focused on determining the factors influencing visitation to KKGP among domestic visitors. The multiple regression function is applied to identify the causal relationships between the dependent variable (visitation rate) and 13 independent variables. Five factors are found to be significant at 5% level, which include travel cost to KKGP, education years of tourists, cost of travelling time, monthly income and tourists’ perception on KKGP. The results of the study could be used to assist the management in making decision for the development of services and products in KKGP in the future.